2000
DOI: 10.1096/fasebj.14.2.391
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic immunization allows the expression of preATF‐saporin chimeric toxin in eukaryotic cells

Abstract: In this work, we have devised an intracellular immunization strategy for the expression in high amounts of ATF-saporin, a targeted chimeric toxin constituted by the ATF receptor binding domain of human urokinase and the plant ribosome-inactivating protein saporin, which has been shown to be highly cytotoxic to target cells. This strategy may allow the production of highly toxic secretory proteins in eukaryotic cells, avoiding cell suicide caused by autointoxication. The procedure consists of equipping host cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
(55 reference statements)
1
24
0
Order By: Relevance
“…21 Also SAP-based chimeric toxins targeting either receptors highly expressed on the surface of cancer cells like those for basic fibroblast growth factor (bFGF) or for human urokinase or specific prostate antigen expressing cells exerted high specific cytotoxic activity. 17,19,25,26 However, the cytotoxicity of all these compounds depends not only on tumor accessibility and penetration but also on an efficient internalization, intracellular sorting and release of catalytically active toxin domains into the cytoplasm. Another common drawback of such an approach is the resistance acquired by cancer cells caused by either loss or downregulation of specific receptors by autocrine ligands which, thus, reduce binding and internalization of the recombinant toxin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Also SAP-based chimeric toxins targeting either receptors highly expressed on the surface of cancer cells like those for basic fibroblast growth factor (bFGF) or for human urokinase or specific prostate antigen expressing cells exerted high specific cytotoxic activity. 17,19,25,26 However, the cytotoxicity of all these compounds depends not only on tumor accessibility and penetration but also on an efficient internalization, intracellular sorting and release of catalytically active toxin domains into the cytoplasm. Another common drawback of such an approach is the resistance acquired by cancer cells caused by either loss or downregulation of specific receptors by autocrine ligands which, thus, reduce binding and internalization of the recombinant toxin.…”
Section: Discussionmentioning
confidence: 99%
“…11 and in anticancer therapy, to construct immunotoxins or ligand toxins [18][19][20][21] and SAP complementary DNA (cDNA) has been used for expressing targeted recombinant chimeras. 17,[22][23][24][25] When a SAP-based secretory chimera was expressed in Xenopus laevis oocytes, total inhibition of cellular protein synthesis was observed that could be restored only by supplementing neutralizing anti-SAP antibodies into the oocyte cytosol, 26 indicating that, although almost all of the chimera was secreted, the few molecules escaping from the secretory pathway were sufficient to inactivate protein synthesis in the host cells.…”
mentioning
confidence: 99%
“…To detect a functional role for ERAD in the intoxication path of exogenously applied saporin, toxin dose response curves were compared in wild-type and mutant CHO cell lines, exhibiting defects in the ERAD pathway affecting a number of ER-translocating toxins including ricin, but no differences could be detected, while evidence for escape from endosomal compartment(s) both for saporin and for a urokinase-saporin conjugate was provided [75]. The high cytotoxicity towards mammalian cells of chimeras containing saporin or other type I RIPs clearly indicates that these toxins have the ability to reach the cytosol after being internalized [76]. Thus, although different lines of evidence indicate that saporin and other type I RIPs can efficiently cross cellular membranes, the site(s) and mechanism of translocation might be quite different from those used by the catalytic subunits of type II RIPs.…”
Section: Rip Intoxication Routes In Mammalian Cellsmentioning
confidence: 99%
“…27 Recently, some groups have reported the successful synthesis of immunotoxins in eukaryotic cells in vitro and in vivo. [28][29][30][31][32] These researchers found that the transfected eukaryotic cells retained their viability while continuously secreting immunotoxin proteins. Compared with the bacterial expression system for proteins in eukaryotic systems, there is no size limitation on the proteins expressed in the system.…”
Section: Discussionmentioning
confidence: 99%